DETERMINING THE IDEOLOGICAL KNOWLEDGE OF THE SCHOOL STUDENTS - Muminov Maхamatkarim (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article states the negative effect of globalization condition on spirituality of youth. The ideological outlook of students is regularly explored to prevent spiritual threats. The state of ideological upbringing of students is analyzed and the results are monitored. In this way, it will contribute to the peace and stability of the country.